EXEGESIS OF QUR’ANIC VERSES CONCERNING ZAKAT, INFAQ, AND SADAQAH, AND THEIR IMPLICATIONS FOR THE SOCIO-ECONOMIC GOVERNANCE OF THE MUSLIM COMMUNITY - Safaruddin Safaruddin (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2026)
This study aims to analyze the interpretation of verses on zakat, infaq, and shadaqah and explore their implications for the socio-economic management of the Muslim community in a modern context. This study uses a qualitative approach based on literature review with primary sources in the form of verses from the Qur'an related to ZIS and their interpretations in a number of classical and contemporary tafsir books, as well as secondary sources in the form of Islamic economics literature and ZIS institutional documents. The data were analyzed thematically, contextually, and comparatively to identify the normative principles of ZIS and their relevance to the management practices of zakat, infaq, and shadaqah institutions. The results of the study show that the verses on ZIS not only stipulate individual worship obligations, but also contain principles of distributive justice, priority for vulnerable groups, clarity of recipient targets, recognition of the institutional role of amil, and demands for trust, transparency, and professionalism in the management of public assets. Further analysis shows that these principles can be operationalized in the form of regulatory strengthening, accounting and reporting standardization, utilization of digital technology, and development of empowerment-oriented ZIS programs. This article concludes that the interpretation of the verses on ZIS provides a solid normative framework for building a more adaptive, accountable, and socially just ZIS governance system, while bridging the gap between interpretive discourse and institutional practice in the field.